2009
DOI: 10.1186/1475-2875-8-294
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of a flow-cytometry-based assessment of in vitro Plasmodium falciparum drug sensitivity

Abstract: BackgroundRecently developed Sybr Green-based in vitro Plasmodium falciparum drug sensitivity assays provide an attractive alternative to current manual and automated methods. The present study evaluated flow cytometry measurement of DNA staining with Sybr Green in comparison with the P. falciparum lactate dehydrogenase assay, the tritiated hypoxanthine incorporation assay, a previously described Sybr Green based plate reader assay and light microscopy.MethodsAll assays were set up in standardized format in 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…A previous study done in Australia pointed to the difference of sensitivity of the Flow cytometry assay, the Sybr Green plate reader assay, the Plasmodium falciparum lactate dehydrogenase assay and light microscopy used in in vitro antiplasmodial activity assessments. 24 …”
Section: Discussionmentioning
confidence: 99%
“…A previous study done in Australia pointed to the difference of sensitivity of the Flow cytometry assay, the Sybr Green plate reader assay, the Plasmodium falciparum lactate dehydrogenase assay and light microscopy used in in vitro antiplasmodial activity assessments. 24 …”
Section: Discussionmentioning
confidence: 99%
“…In practice, detection of ring stages with non-GFP-fluorescent lines may require the application of an alternative staining method such as the combination of thiazole orange and hydroethidine (44) or Hoechst 33342 and (45). Previous studies have reported an encouraging correlation between flow cytometry and microscopy counts of drug-treated cultures in vitro (45,46) as well as application of flow cytometry to assess drug inhibition of late-stage parasite development (47). In this study, the correlation between numbers of free merozoites and parasite growth inhibition (newly invaded rings) has been described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Artesunate has been reported to have an IC 50 of 108 nM for gametocytes (stage IV-V) when assayed by Giemsa smear [8], but the effect of DHA against gametocytes has not been published previously. Although DHA is more efficacious than the other drugs tested, the effective dose against asexual parasites is much lower than that required to kill gametocytes and this is reflected in the ability of gametocytes to remain infectious to mosquitoes for a week after artemisinin treatment [10, 1819]. Together these results demonstrate that alamarBlue can be used to efficiently screen compounds for gametocytocidal activity.…”
Section: Gametocytocidal Activity Of Common Anti-malarial Drugsmentioning
confidence: 99%